Purification, crystallization and preliminary crystallographic analysis of the 16S rRNA methyltransferase RsmI from Escherichia coli. Issue 9 (1st September 2014) - Zhao, Mohan; Wang, Li; Zhang, Heng; Dong, Yuhui; Gong, Yong; Zhang, Linbo; Wang, Jian
Abstract : RsmI and RsmH are AdoMet‐dependent methyltransferases that are responsible for the 2′‐ O ‐methylation and N 4 ‐methylation of C1402 of Escherichia coli 16S rRNA, respectively. Modification of this site has been found to play a role in fine‐tuning the shape and function of the P‐site to increase the decoding fidelity. It is interesting to study the mechanism by which C1402 can be methylated by both RsmI and RsmH. The crystal structure of RsmH in complex with AdoMet and cytidine has recently been determined and provided some implications for N 4 ‐methylation of this site. Here, the purification and crystallization of RsmI as well as its preliminary crystallographic analysis are reported. Co‐crystallization of RsmI with AdoMet was carried out by the sitting‐drop vapour‐diffusion method and X‐ray diffraction data were collected to 2.60 Å resolution on beamline 1W2B at BSRF. The crystal contained three molecules per asymmetric unit and belonged to space group C 2, with unit‐cell parameters a = 121.9, b = 152.5, c = 54.2 Å, β = 93.4°.